HUMAN RESOURCE DEVELOPMENT AND SUSTAINABLE WORKPLACE IN THE ORGANIZED PRIVATE SECTOR: A STUDY OF TONIMAS NIGERIA LIMITED, ABA, ABIA STATE, 2020-2025 - Ogbonnaya Ejim, Onyebuchi; Sunday Umeh, Chijioke; Favour Okoli, Ezinne (African Journal of Social and Behavioural Sciences, 2026)
This study examined the impact of human resource development on a sustainable workplace in the organized private sector, using Tonimas Nigeria Limited, Aba, Abia State as a focal point. The study sought to determine the impacts of employees’ training and development, well-being, and performance management practices on a sustainable workplace in the company. A survey research design was adopted. Using the “Taro Yamane formula,” 92 respondents were randomly selected as the sample size out of 119 staff of Tonimas Nigeria Limited, Aba. A simple random sampling procedure was used: every member had an equal chance of being selected by lottery. An instrument titled Human Resource Development and Sustainable Workplace Questionnaire (HRDSWQ) structured in a Four-point Likert format, with a reliability coefficient of 0.80 obtained using Cronbach’s Alpha, was administered for data collection. The data collected were analyzed using percentages, mean, and the hypotheses were tested with Chi-square (x2). The study is anchored in Resource-Based View Theory. It was revealed that employees’ training and development, well-being, and performance management practices could enhance a sustainable workplace in the company. It was recommended that the personnel officers should prioritize human resource development indicators such as employees’ training and development, employees’ engagement and well-being, as well as employees’ performance management strategies, which are capable of creating an attractive and sustainable workplace practice for organic productivity in Tonimas Nigeria Limited, Aba, Abia State.